The Role of Mycorrhizal-Assisted Phytomining in the Recovery of Raw Materials from Mine Wastes - Scotti, Adalgisa (2022)
In recent years, critical and secondary raw materials (CRMs and SRMs, respectively) have received great interest within the circular economy model. In this work, the mycorrhizal-assisted phytomining (MAP) system, composed of Helianthus annuus–arbuscular mycorrhizal fungus Rhizophagus intraradices–Zn-volcanic ashes, was applied in bioreactors for the recovery of CRMs (Sr, P) and SRMs (Cr, Zn, Cu, Mn, Rb, Ni) from mining wastes of the Los Cóndores mine (Argentina). Our results showed high bioaccumulation of Sr, P, Mn, and Zn in the aerial tissues, and a high root-to-shoot translocation for Mn (4.02) > Sr > P > Rb > Zn (0.84). Mycorrhization treatment increased the root-to-leaf translocation for Cr and P and prevented translocation towards flower tissues in most elements. The estimated bioextracting potential of the MAP system (290 plants) in a vegetable depuration module (VDM) ranged from 158 mg/m3 P > Zn > Mn > 15.1 mg/m3 Sr. We demonstrated a promising and cost-effective biotechnology applicable in agronomical practices, given the exclusion of toxic elements in flower parts, as well as for the recovery of CRMs and SRMs by hydrometallurgy from plant biomass.